Professional–Collector Collaboration: Moving beyond Debate to Best Practice. Issue 1 (February 2022) - Pitblado, Bonnie L.; Rowe, Matthew J.; Schroeder, Bryon; Thomas, Suzie; Wessman, Anna
Abstract: This article introduces the first of what will ultimately be two collections of case studies in archaeologist–responsible/responsive artifact collector collaboration. Focused on the United States, the articles in this issue of Advances in Archaeological Practice share the thoughts and experiences of archaeologists representing diverse employment sectors (compliance, agency, museum, and university), artifact collectors, and members of descendant communities. Research areas extend from California to Virginia and from Ohio to the Texas/Mexico border. The breadth of the writers' backgrounds and their focal regions reinforce the wide applicability of collaborative best practices. Every author explicitly treats two subjects: (1) the intersection of their work with the Society for American Archaeology's (SAA) recently published guidelines for ethical professional–collector collaboration, and (2) their own practical suggestions for establishing and nurturing those relationships. This introductory article provides an overview of each of the other contributions, notes how the contributions articulate with the SAA guidelines, and offers its own, mostly philosophical suggestions for prospective members of professional–collector collaborations.